1987
DOI: 10.1152/jappl.1987.62.2.574
|View full text |Cite
|
Sign up to set email alerts
|

Airflow-induced bronchoconstriction: role of epithelium and eicosanoid mediators

Abstract: We examined the role of cyclooxygenase-derived metabolites and epithelial cells in airflow-induced bronchospasm. Male dogs were anesthetized and collateral system resistance (Rcs) was measured with the wedged-bronchoscope technique. A 2-min high flow challenge with dry air in nine animals produced a mean increase in Rcs of 69 +/- 13% (SE). After treatment with indomethacin (5 mg/kg), the response was significantly attenuated; Rcs increased only 40 +/- 8%. Bronchoalveolar lavage performed 5 min after a dry air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 0 publications
7
36
0
Order By: Relevance
“…Previous studies have demonstrated that canine peripheral airways were nonrefractory to dry air [10,11,13] and hypertonic aerosol challenges [23]. In this study, we found that AIB was unaffected by a preceding hypertonic aerosol challenge ( fig.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Previous studies have demonstrated that canine peripheral airways were nonrefractory to dry air [10,11,13] and hypertonic aerosol challenges [23]. In this study, we found that AIB was unaffected by a preceding hypertonic aerosol challenge ( fig.…”
Section: Discussionsupporting
confidence: 52%
“…The dried sample was then reconstituted to 1.0 ml with 0.1% gelatin-phosphate buffered saline. The mediator was then measured using a competitive radioimmunoassay (RIA) system, as described previously [11,30]. Assays were sensitive from 5-20 pg·0.1 ml -1 and crossreactivity of all antibodies was <1% with PGE 1 , PGE 2 , 6-keto PGF 1 , PGF 2α , and TxB 2 [31].…”
Section: Mediator Concentrations In Balfmentioning
confidence: 99%
See 3 more Smart Citations